Effectiveness of transcranial direct current stimulation preceding cognitive behavioural management for chronic low back pain: sham controlled double blinded randomised controlled trial. (16th April 2015) - Luedtke, Kerstin; Rushton, Alison; Wright, Christine; Jürgens, Tim; Polzer, Astrid; Mueller, Gerd; May, Arne
Abstract : Objective To evaluate the effectiveness of transcranial direct current stimulation alone and in combination with cognitive behavioural management in patients with non-specific chronic low back pain. Design Double blind parallel group randomised controlled trial with six months' follow-up conducted May 2011-March 2013. Participants, physiotherapists, assessors, and analyses were blinded to group allocation. Setting Interdisciplinary chronic pain centre. Participants 135 participants with non-specific chronic low back pain >12 weeks were recruited from 225 patients assessed for eligibility. Intervention Participants were randomised to receive anodal (20 minutes to motor cortex at 2 mA) or sham transcranial direct current stimulation (identical electrode position, stimulator switched off after 30 seconds) for five consecutive days immediately before cognitive behavioural management (four week multidisciplinary programme of 80 hours). Main outcomes measures Two primary outcome measures of pain intensity (0-100 visual analogue scale) and disability (Oswestry disability index) were evaluated at two primary endpoints after stimulation and after cognitive behavioural management. Results Analyses of covariance with baseline values (pain or disability) as covariates showed that transcranial direct current stimulation was ineffective for the reduction of pain (difference between groups on visual analogue scale 1 mm (99% confidence interval −8.69 mm to 6.3 mm; P=0.68)) and disability (difference between groups 1 point (−1.73 to 1.98; P=0.86)) and did not influence the outcome of cognitive behavioural management (difference between group 3 mm (−10.32 mm to 6.73 mm); P=0.58; difference between groups on Oswestry disability index 0 point (−2.45 to 2.62); P=0.92). The stimulation was well tolerated with minimal transitory side effects. Conclusions This results of this trial on the effectiveness of transcranial direct current stimulation for the reduction of pain and disability do not support its clinical use for managing non-specific chronic low back pain. Trial registration Current controlled trials ISRCTN89874874 .